Optical communication theory and techniques - Forestieri, Enrico (Springer, 2015)
A collection of papers dealing with the theoretical aspects of optical communications. This work is divided into 4 parts: Information and Communication Theory for Optical Communications; Coding Theory and Techniques; Characterizing, Measuring, and Calculating Performance in Optical Fiber Communication Systems; and Modulation Formats and Detection.